Recent Applications of Molecularly Imprinted Polymers (MIPs) on Micro-extraction Techniques. Issue 1 (2nd January 2018) - Li, Guizhen; Row, Kyung Ho
Abstract : Microextraction is considered as one of the most critical steps in the entire analytical process because it can effectively remove interference and pre-concentrate the target analytes. Molecularly imprinted polymers (MIPs) are synthetic polymers with a predetermined selectivity for a given analyte, or group of structurally related compounds, which are excellent materials for sample preparation in the process of microextraction owing to their high selectivity and ability. This review provides a critical overview of the synthesis and characterization of MIPs, with a focus on recent applications in the field of solid-phase microextraction (SPME) and liquid-phase microextraction (LPME). The advantages and drawbacks of the applications of MIPs used in SPME and LPME as well as the future expected trends are also discussed.